Rapid Inhibition of Neurons in the Dorsal Motor Nucleus of the Vagus by Leptin - Williams, K. W. (2006)
The peptide leptin conveys the availability of adipose energy stores to the brain. Increasing evidence implicates a significant role for extrahypothalamic sites of leptin action, including the dorsal vagal complex, a region critical for regulating visceral parasympathetic function. The hypothesis that leptin suppresses cellular activity in the dorsal motor nucleus of the vagus nerve (DMV) was tested using whole-cell patch-clamp recordings in brainstem slices. Leptin caused a rapid membrane hyperpolarization in 50% of rat DMV neurons. Leptin also hyperpolarized a subset of gastric-related neurons (62%), identified after gastric inoculation with a transneuronal retrograde viral tracer. The hyperpolarization was associated with a decrease in input resistance and cellular responsiveness and displayed characteristics consistent with an increased K(+) conductance. Perfusion of tolbutamide (200 μM) reversed the leptin-induced hyperpolarization, and tolbutamide or wortmannin (10–100 nM) prevented the hyperpolarization, indicating that leptin activated an ATP-sensitive K(+) channel via a phosphoinositide-3-kinase-dependent mechanism. Leptin reduced the frequency of spontaneous and miniature excitatory postsynaptic currents (EPSCs), whereas inhibitory postsynaptic currents (IPSCs) were largely unaffected. Electrical stimulation of the nucleus tractus solitarii (NTS) resulted in constant-latency EPSCs, which were decreased in amplitude by leptin. The paired-pulse ratio was increased, suggesting leptin effects involved activation of receptors presynaptic to the recorded neuron. A leptin-induced suppression of EPSCs, but not IPSCs, evoked by focal photolytic uncaging of glutamate within the NTS was also observed, supportive of leptin effects on the glutamatergic NTS projection to the DMV. Therefore, leptin directly hyperpolarized and indirectly suppressed excitatory synaptic activity to DMV neurons involved in visceral regulation, including gastric-related neurons.